Relict periglacial soils on Quaternary terraces in the Central Ebro Basin (NE Spain). (30th June 2019) - Rodríguez‐Ochoa, Rafael; Olarieta, José R.; Santana, Asier; Castañeda, Carmen; Calle, Mikel; Rhodes, Ed; Bartolomé, Miguel; Peña‐Monné, José L.; Sancho, Carlos
Abstract: Pedofeatures associated with ancient cold climatic conditions have been recognized in soils on terraces in the Monegros area (central Ebro Basin, Spain), at a latitude of 41°49′N and an altitude of 300 m a.s.l. Eleven soil profiles were described on fluvial deposits corresponding to the most extensive terrace (T5) of the Alcanadre River, Middle Pleistocene in age (MIS8–MIS7). Each soil horizon was sampled for physical, chemical, mineralogical and micromorphological analyses. Macromorphological features related to pedocryogenic processes were described: involutions, jacked stones, shattered stones, detached and vertically oriented carbonatic pendents, fragmented carbonatic crusts, laminar microstructures, succitic fabric, silt cappings on rock fragments and aggregates, and irregular, broken, discontinuous and deformed gravel and sandy pockets. Accumulations of Fe–Mn oxides, dissolution features on the surface of carbonatic stones, and calcitic accumulations were identified related to vadose–phreatic conditions. The observed periglacial features developed under cold environmental conditions in exceptional geomorphic and hydrological conditions. This soil information may have potential implications in studies of paleoclimate in the Ebro Valley as well as in other Mediterranean areas.